2012
DOI: 10.1109/tps.2012.2207130
|View full text |Cite
|
Sign up to set email alerts
|

From RONS to ROS: Tailoring Plasma Jet Treatment of Skin Cells

Abstract: Finding a solution for air species contamination of atmospheric pressure plasmas in plasma medical treatment is a major task for the new field of plasma medicine. Several approaches use complex climate chambers to control the surrounding atmosphere. In this paper, ambient species are excluded in plasma-human-skin-cell treatment by ensheathing the plasma jet effluent with a shielding gas. Not only does this gas curtain protect the plasma jet effluent from inflow of air species but it also, more importantly, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 20 publications
3
143
0
Order By: Relevance
“…Additionally, H 2 O 2 increased the relative phosphorylation of MEK 1/2 (1.8-fold) and ERK 1/2 (1.3-and 1.4-fold), consistent with Bhatt et al, who showed that ERK 1/2 can be induced in human monocytes by exogenous reactive oxygen species such as H 2 O 2 [28]. Since H 2 O 2 is generated in plasma-treated liquids, it is hypothesized to be one of the species activating the MEK-ERK pathway [29].…”
Section: Plasma-mediated Regulation Of Mapk Signaling Pathwayssupporting
confidence: 88%
“…Additionally, H 2 O 2 increased the relative phosphorylation of MEK 1/2 (1.8-fold) and ERK 1/2 (1.3-and 1.4-fold), consistent with Bhatt et al, who showed that ERK 1/2 can be induced in human monocytes by exogenous reactive oxygen species such as H 2 O 2 [28]. Since H 2 O 2 is generated in plasma-treated liquids, it is hypothesized to be one of the species activating the MEK-ERK pathway [29].…”
Section: Plasma-mediated Regulation Of Mapk Signaling Pathwayssupporting
confidence: 88%
“…Additionally, we found that the trend of VUV induced oxygen free radicals in complex liquids and the inhibition of human skin cells' viability 42 shows exactly the contrary behavior in dependency of the surrounding atmosphere. Thus, it can be claimed that the VUV generated ROS in the liquid are not the dominating species for inhibition of skin cell viability.…”
mentioning
confidence: 83%
“…This is an expected result and correlates well with the known chemistry of jet based plasmas and their interaction with liquids. 37,48 However, the impact of these nitrogen species on cell proliferation rate is limited. Sodium nitrite did not affect HaCaT cell proliferation rates up to 2000 lM under test conditions [ Fig.…”
Section: B Argon Rf Plasma Case and Comparison With Kinpenmentioning
confidence: 99%